If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 8x + (16) Reorder the terms: 4 + 5x = 8x + (16) 4 + 5x = 8x + 16 Reorder the terms: 4 + 5x = 16 + 8x Solving 4 + 5x = 16 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 4 + 5x + -8x = 16 + 8x + -8x Combine like terms: 5x + -8x = -3x 4 + -3x = 16 + 8x + -8x Combine like terms: 8x + -8x = 0 4 + -3x = 16 + 0 4 + -3x = 16 Add '-4' to each side of the equation. 4 + -4 + -3x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 16 + -4 -3x = 16 + -4 Combine like terms: 16 + -4 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 5z+12=3z | | -6-5x=-6-6x | | -7=x-4x | | 3f(-2)= | | 2/3*-2=0 | | -(2+7b)-6(b-4)= | | 6x+5+x=2+2x-17 | | 12=3x-x | | 12=3(-n+1) | | 2.9q-1.6-2.3q=-0.4q-5.9 | | 126=-2(1-8m) | | 2x^2-4x-96= | | 133=.7(200+x) | | 2z-3=-0 | | 7x-10=-2x-5 | | 4(7v+8)-5(1-8v)= | | 3n+8=3(2+n) | | 6(4-4n)=-22-n | | 2x-6x=-16 | | .15(1.5+2x)=11.50 | | (x+18)(x-12)= | | -(3x+3)+3(2-x)=1+x+2-x | | 2(x-1)=2+2(1+7x) | | 56v^2-17v=3 | | -x+1+8x=-2+4x+15 | | a+(6+a)=36 | | -60z-0.5=-70z+1.9 | | -5y+1=-6y+4 | | 7w=.125 | | -3,(n-3)+4(n+4)= | | 2x+4x=-16 | | 5(3x-5)+x=2(4x-1)+1 |